Injectable and Conductive Polyurethane Gel with Load-Responsive Antibiosis for Sustained Root Canal Disinfection - Bo Mu; Xiaoyu Lei; Yinglong Zhang; Jingzheng Zhang; Qingda Du; Yuping Li; Dongyu Huang; Li Wang; Jidong Li; Yubao Li; Yi Zuo (Gels)
To address the limitations of conventional antibacterial therapies, we developed an injectable, conductive polyurethane-based composite gel system for sustained root canal disinfection. This gel incorporates piezoelectric nanoparticles (n-BaTiO3) and conductive segments (aniline trimer, AT) within a polyurethane matrix, which synergistically interact with a static antimicrobial agent (n-ZnO) to achieve dynamic, mechano-responsive antibacterial activity. Under cyclic compression (simulating mastication), the piezoelectric gels exhibited enhanced electroactivity via the mechano-electric coupling effect, generating 2-fold higher voltage and a 1.8–1.9× increase in current compared to non-piezoelectric controls. The dynamic electroactivity of the gels enabled superior long-term performance, achieving 92–97% biofilm eradication, significantly higher than the static n-ZnO-only gel (88%). XPS and UV-vis spectroscopy analyses confirmed mechano-electrochemically amplified reactive oxygen species (ROS) generation, which contributed to improved biofilm disruption. The ISO-compliant gel provides durable, load-responsive disinfection while maintaining good biocompatibility, offering a promising solution to prevent post-treatment reinfection.